Penerapan Metode Prototype Pada Sistem Informasi Pengelolaan Data Tamu Hotel - Dody Pria Sagita; Alam Supriyatna (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
The management of guest data at Hotel Gerbera is currently still by recording books, starting from the check-in process which is done by filling out the registration sheet, then inputting guest data who has checked in in the Guest In The House data table using Microsoft Excel and writing money data. Incoming cash payments, debit / credit and receivables per shift in the Daily Cashier Sheet. This kind of data input process is less effective because it takes a lot of time to enter guest data into each different report form. The research with the title "Gerbera Hotel Guest Data Management Information System Using Prototype Method" has a problem formulation of how to manage the Gerbera Hotel guest database and how to apply the prototype method to the Gerbera Hotel Guest Data Management Information System. The purpose of this research is for the effectiveness of time in the process of managing guest data for the receptionist, storing guest data is well organized by the system, and making it easier for the receptionist to find data on guests who have checked in. This study uses the prototype method. The development of the prototype method starts from the stage of gathering user requirements and analysis, rapid design, building prototypes, evaluating prototypes, changing designs and prototypes, until customers are satisfied, then large-scale development. Based on the research conducted, it is concluded that to manage guest data so that it is stored properly in the database is to develop an information system for managing guest data at Hotel Gerbera. The test results of the Gerbera Hotel guest data management information system are in the very feasible category with a percentage value of 92%.